Evaluating the positive drinking consequences questionnaire: Support for a four-factor structure and measurement invariance. (3rd September 2019) - Jordan, Hallie R.; Carroll, Mallorie G.; Mohn, Richard S.; Villaorsa-Hurlocker, Margo C.; Capron, Daniel W.; Madson, Michael B.
ABSTRACT: The 14-item Positive Drinking Consequences Questionnaire (PDCQ) was developed to assess experienced positive drinking consequences. The present study sought to advance the psychometric evaluation of the PDCQ via exploratory and confirmatory factor analyses, measurement invariance, criterion-related validity, and internal consistency. Participants were 1, 088 traditional-age college students (81% female) who reported drinking in the past month. Exploratory factor analysis supported a four-factor model (i.e. Sociability, Tension Reduction, Liquid Courage, and Sexual Enhancement), and the confirmatory factor analysis indicated the four factors loaded on a higher-order factor ("PDCQ"). Invariance testing supported invariance for the PDCQ across gender. The PDCQ was positively associated with alcohol use and alcohol-related negative consequences, and negatively associated with protective behavioral strategies. Finally, the four factors of the PDCQ were discriminant from positive expectancies. Collectively, positive drinking consequences appear to be more nuanced than originally conceptualized. Evaluation of specific types of positive drinking consequences may assist in more precise prevention and intervention efforts in the future.